About the divine, religion and women in Bacon - Solano Villareal, Diana (2020)
This article deals with the themes of the divine, religion and women, in theBacon’s books: The Advance of Learning, Preparation towards a Naturaland Experimental History, Valerius terminus: Or the Interpretation of Natureand Dignitate et Augmentis Scientiarum, in our days. The above from thetheory of the group Modernity / Coloniality, in colonial studies and generalfeminist theory.